Iddah of A Pregnant Woman Following The Death of Her Husband: A Study of Ta’arudh Al-Adillah - Arzam, Arzam; Ridha DS, Muhammad; Natardi, Natardi; Witro, Doli (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
One of the consequences that must be endured by women after divorce, the divorce of thalaq, or divorce due to death is iddah. Enforcement of iddah for women after the divorce is not Islamic law-oriented but had existed before Islam came. In general, two verses explain about iddah which are considered ta’arudh al-adillah (considered contradictory) namely surah al-Baqarah verse 234 states that women whose husbands’ deaths receive iddah for four months ten days and surah ath-Thalaq ayat 4, Allah states that pregnant women get iddah until they give birth to their children. Therefore, this study aims to examine the iddah law of a pregnant woman whose husband has died based on the instructions of surah al-Baqarah verse 234 and surah ath-Thalaq verse 4, using ta’arudh al-adillah. This type of research is a qualitative research that is literature research. Sources of data in this research involved books, scientific journals, articles, internet, legal products, and other forms of written documents relating to iddah. Methods of data collection in this research employed reading, comparing, examining as many data sources as possible. Data analysis methods in this research included data reduction, data presentation, and conclusion. For more profound analysis results, this study also performed data analysis techniques, the bayani method, the ta’lili method, and the istislahi method. The results showed that the iddah period for a woman whose husband dies according to surah al-Baqarah verse 234 is four months and ten days. This law applies if the woman is not pregnant. However, the provisions for pregnant women are more specifically specified in surah ath-Thalaq verse 4, because the provisions of pregnancy have been specified (takhsis) in surah ath-Thalaq verse 4.